Health services restructuring in Alberta and the 2009 pandemic influenza—An untimely concurrence - Musto, Richard (Healthc Manage Forum, 2020)
In the last 12 years, every Canadian province and territory has undertaken significant health services restructuring, with the pace of change accelerating recently. When the H1N1 Pandemic Influenza (PI) hit Alberta in the spring of 2009, the province had just begun a restructuring of health services of a scale unprecedented in Canada. The new province-wide entity, Alberta Health Services (AHS), was faced with mounting an effective response to a global communicable disease outbreak during a time of great organizational flux. In this retrospective, the authors reflect on challenges and opportunities presented during the AHS PI response related to the coordination of public health, laboratory services, emergency and disaster management, communications, and health services delivery. Lessons learned are shared that may be helpful to other provinces and territories as they continue to evolve their systems, so that they may be better prepared to respond to an untimely event such as a pandemic.